FROM FORCED CULTIVATION TO INDUSTRIALISATION: SOCIO ECONOMIC IMPACTS AND THE EMERGENCE OF THE KALIBAGOR SUGAR FACTORY: Dari Tanam Paksa Ke Industrialisasi: Dampak Sosial Ekonomi Dan Kemunculan Pabrik Gula Kalibagor - Faizal Jefri Pratama; Arifin Suryo Nugroho (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines the forced cultivation system or culturstelsel in Banyumas until the era of industrialisation, focusing on the socioeconomic impact of the Kalibagor Sugar Factory. This study employs historical methods, including the stages of heuristics, source criticism, interpretation, and historiography, utilizing primary sources such as colonial archives and supported by secondary sources. The findings of this study indicate that Cultuurstelsel in Banyumas was an adaptation of the land tax policy, which aimed to produce export commodities and increase colonial revenue. Established in 1839, the Kalibagor Sugar Factory functioned as the main hub for the implementation of this system through the processing of sugas cane from surrounding village lands. Entering the era of industrialisation, the use of steam engines brought major changes to the socio economic order, as the wage labour system replaced the traditional agrarian pattern. This research concludes that the Kalibagor Sugar Factory transformed the pattern of Banyumas society from agrarian to industrial, as well as creating economic dependence by giving rise to a capitalist system and social inequality between the local elite and workers.